Pelatihan Pengolahan Jahe Menjadi Minyak Atsiri Dengan Teknik Penyulingan Pada Kelompok Petani Desa Junrejo Kecamatan Junrejo Kota Batu - Muddarisna, Nurul; Rahayu, Yekti Sri; Su?i, Mohamad (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2018)
Ginger farmers in the Junrejo village, Junrejo sub district, Batu,  generally sell ginger in fresh form which hasa risk of low profit.  Storage of fresh ginger for a long time can reduce the content of essential oils resulting in decreasedquality and selling value.  One of techniques that can be used to minimize the risk is to process the fresh ginger into theessential oils. The purpose of this program was to provide counseling about post-harvest handling of ginger and trainingof fresh ginger processing into essential oils with distillation techniques. The target of this program was to improve skillsof  ginger farmers to distillate fresh ginger rhizome into essential oil. During the training, farmers showed enthusiasmand high spirits in following the training phase. The results of calculation of essential oil content of two types of freshginger used in the training was 0.15% in emprit ginger and 0.2% in red ginger. The results of laboratory analysis ofessential oil characteristic of ginger emprit  showed that the emprit ginger produced by Junrejo village farmers consisted of acid value, specific gravity (at 250C) and refractive index (at 250C) of 0.98% ; 1.498; and 0.98, respectively